Investigation of copper powder characteristics in binder jetting using a rheometer - Hussain Mohamed Faizal (Nanyang Technological University, 2023)
Binder jetting is a type of 3D printing technique that uses a binder to bond powder materials together to create a component close to its net shape. This technique can be challenging for processing copper because an optimal feedstock has not yet been identified to produce dense copper parts. Therefore, identifying specific powder characteristics is necessary to achieve optimal print performance. ASTM powder standards may not fully evaluate binder jetting's powder behaviour during printing, thus FT4 Rheometer was used evaluate powder behaviour during the print Firstly, two types of copper powder with different particle size distributions, fine (D50: 13.89 µm) and coarse (D50: 25.85 µm) powder were evaluated using FT4 Rheometer (Flow Rate Index, Stability Index, Cohesion, Wall Friction Angle, Compressibility) and ASTM standard (particle size distribution, flowability, apparent and tapped density). Next, the ExOne Innovent printer was utilized to evaluate the powders' printing performance and identify any differences in the printing quality between the two powders. The study aimed to identify the powder characteristics that perform well in the binder jetting process. The results demonstrate the flexibility of FT4 Rheometer to identify the characteristics of powder that will perform well in ExOne Innovent printer. Fine copper powder fabrication was challenging due to poor flowability, resulting in cracks and layer shifting during printing. Results from both the FT4 Rheometer and ASTM tests confirmed poor flowability, indicating higher cohesion and flow rate index values for the fine powder, consistent with the poor flowability results from the Hall flow or Carney flow tests in the ASTM standard. The combination of FT4 Rheometer and ASTM standard measurements is effective for evaluating the performance of powders in the ExOne Innovent printer.